Performance and analysis of ceramic slip rotary moulding for fine bone China product / Norazne Nasir - Nasir, Norazne (2019)
One of the method to produce ceramic product is by using slip casting process. However, the process produces waste from the excess slip and takes a long time to complete the process. Alternatively, a new process is being established by combining the traditional slip casting technique and existing polymer rotary moulding concept called Ceramic Slip Rotary Moulding (CSRM).